The Digital Public Domain: Foundations for an Open Culture - Dulong de Rosnay, Melanie and Juan Carlos De Martin (eds.) (Open Book Publishers, 2012)
Digital technology has made culture more accessible than ever before. Texts, audio, pictures and video can easily be produced, disseminated, used and remixed using devices that are increasingly user-friendly and affordable. However, along with this technological democratization comes a paradoxical flipside: the norms regulating culture's use — copyright and related rights — have become increasingly restrictive. This book brings together essays by academics, librarians, entrepreneurs, activists and policy makers, who were all part of the EU-funded Communia project. Together the authors argue that the Public Domain — that is, the informational works owned by all of us, be that literature, music, the output of scientific research, educational material or public sector information — is fundamental to a healthy society. The essays range from more theoretical papers on the history of copyright and the Public Domain, to practical examples and case studies of recent projects that have engaged with the principles of Open Access and Creative Commons licensing. The book is essential reading for anyone interested in the current debate about copyright and the Internet. It opens up discussion and offers practical solutions to the difficult question of the regulation of culture at the digital age.